Evaluating the impact of triple elimination program for mother-to-child transmission of HIV, syphilis, and hepatitis B in Indonesia - Azhali, Buti A.; Setiabudi, Djatnika; Alam, Anggraini (Narra Sains Indonesia, 2023)
Indonesian government launched a triple elimination program to eliminate mother-to-child transmission (MTCT) of human immunodeficiency virus (HIV), syphilis, and hepatitis B in 2018, aiming to increase screening uptake among pregnant women during antenatal visits and to reduce the rates of these infections in children less than 50 per 100,000 live births. Despite this initiative, a thorough assessment of its effectiveness, particularly in Bandung, the capital city of West Java, as one of the most densely populated cities in Indonesia with a high HIV incidence, has yet to be conducted. The aim of this study was to analyze the impact of this triple elimination program in Bandung by assessing the data between 2017 and 2020. Monthly data was obtained from the Health Office of Bandung for four years, including number of screenings done for HIV, syphilis, and hepatitis B, number of confirmed cases and number of pregnant women treated for those infections. Additionally, data on children under 24 months old afflicted by these infections were also collected. Our data indicated an increase in screening coverage for HIV, syphilis, and HBV among pregnant women; however, it remained below the national set benchmarks for screening coverage. Only 59.5% of HIV-positive pregnant women received anti-retroviral therapy in 2020, while merely 25% of syphilis-positive cases were administered benzathine penicillin G. Syphilis screening was correlated with an increase in positive cases among children, suggesting missed opportunities in managing syphilis-positive pregnant women. Furthermore, management of HIV- and syphilis-positive cases had suboptimal outcomes. Data on hepatitis B was not evaluated since it was not available. To achieve the triple elimination program goals, comprehensive coordination among all relevant stakeholders is required, as is continuous monitoring and evaluation.